Investigate various techniques used in theater production, such as lighting, sound design, set design, and costume design, and their impact on dramaturgy - Jabbar Xojanov (Лучшие интеллектуальные исследования, 2024)
Abstract: This paper explores the impact of various theater production techniques, including lighting design, sound design, set design, and costume design, on dramaturgy. Each of these elements plays a crucial role in enhancing the overall theatrical experience, influencing the mood, atmosphere, and visual aesthetics of a performance. Through the strategic use of lighting, sound, sets, and costumes, theater practitioners can deepen character development, highlight thematic motifs, and engage audiences on an emotional and sensory level. By analyzing the interplay between these production techniques and dramaturgy, this paper aims to provide insight into the creative processes involved in bringing a theatrical production to life and the ways in which these elements contribute to the storytelling process.